KINERJA PEMBUATAN AKTA KELAHIRAN - Eva SitiNurkholifah; R Akhmad Munjin; Ginung Pratidina (Jurnal Governansi, 2021)
This study aims to determine the performance of making birth certificates in the Department of Population and Civil Registration of Bogor City. The method used is a description of the analysis with data analysis techniques using the calculation of the Weight Mean Score (WMS). The data collection technique in this study used a questionnaire, and was strengthened by collecting the results of the interview. The theory used in this research is Agus Dwiyanto’s theory which consists of five dimensions, namely productivity, service quality, responsiveness, responsibility and accountability. The results of this study indicate that the performance of making birth certificates shows good results with an average value of 3.87. This is indicated by the results of the analysis of each dimension entering the good category. However, there are still deficiencies and obstacles in the indicators of the availability of infrastructure and service quality.Keywords: Performance, Birth Certificate, Regional Regulation